Reduplication and its function in the poetry A. Malyshko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article considers the replication of both linguistic phenomenon and as a means of performance idiolect A. Malyshko, analyzes various types of phenomena, detected role in the construction of the poem and the ideological and thematic content of the text.
Keywords: reduplication; word formation; a doubling of productivity; derivatives; repeat